Pure flat wear-resistant jade ceramic tile and preparation method thereof
Through multiple glaze coatings and increasing polishing and polishing, combined with low-temperature jade glaze and inkjet printing technology, the transparent wear-resistant glaze polishing formula is adjusted, and the problem of insufficient wear resistance and texture of existing glaze polishing products is solved, achieving high-quality and highly competitive pure flat wear-resistant jade tiles.
Patent Information
- Application Number
- CN202411838333.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
When pursuing bright hair colors and low-cost production, existing glaze-polished products ignore key properties such as wear resistance, stick printing, water ripple and texture, resulting in low product quality and insufficient market competitiveness.
Thick the glaze layer through multiple glaze coating processes, increase the polishing amount to eliminate stick printing and water ripples, and apply low-temperature jade glaze on the base glaze, combining inkjet printing patterns and zirconium white ink, and finally adjust the formula of transparent wear-resistant glaze to improve the hardness and wear resistance of the glaze surface.
It significantly improves the wear resistance and texture of the tiles, eliminates stick printing and water ripples, and improves product quality and market competitiveness.
Smart Images

Figure CN119661254A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic production technology, and in particular relates to a pure flat wear-resistant jade ceramic tile and a preparation method thereof. Background Art
[0002] At present, the product and market competition among ceramic enterprises is very fierce. How to improve product quality and enhance product competitiveness is the key to the survival and development of each enterprise. Unlike foreign markets, the domestic market is still dominated by polished and bright products, especially glazed products. These products have occupied most of the tile market due to their diverse colors and strong decorative effects. However, due to the excessive pursuit of bright colors, transparency and reducing production costs, some companies have ignored the key properties of glazed products such as wear resistance, stick marks, water ripples and texture. In recent years, some companies have begun to pay attention to the improvement of product quality. For example, patent application publication CN111533449A discloses a high-temperature wear-resistant frit, wear-resistant glaze and glazed tiles using it, which suggests replacing feldspar in traditional formulas with high-temperature wear-resistant frits to improve the wear resistance of products. Patent application publication CN112390532A discloses a wear-resistant glaze and a preparation method thereof, and proposes to enhance the wear resistance of the glaze by adding a mixture of carbon fiber and shape memory metal particles. Patent application publication CN103274767A discloses a tile with a flat glaze and a manufacturing method thereof, which combines the screen printing glaze process and the glaze pouring technology to produce a product with a smooth and bright glaze surface. The firing of high-temperature wear-resistant frits, the addition of carbon fiber and shape memory metals greatly increase the production cost of the product, while the production efficiency of screen printing glaze is low and has been gradually replaced. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present invention provides a pure flat wear-resistant jade-like ceramic tile and a preparation method thereof, which not only significantly improves the wear resistance and texture of the ceramic tile, but also effectively solves the problems of stick marks and water ripples that have long plagued polished glaze products, thereby significantly improving product quality and enhancing product market competitiveness.
[0004] The present invention achieves the purpose of eliminating stick marks and water ripples by using multiple glazing processes to thicken the glaze layer and increase the polishing amount. In addition, by optimizing the production process, low-temperature jade glaze is applied on the base glaze, and then inkjet printing patterns and zirconium white ink are performed to enhance the three-dimensional layering and jade texture of the pattern. Finally, the formula of transparent wear-resistant polishing glaze is adjusted to improve the hardness and wear resistance of the glaze surface.
[0005] To solve the above problems, the present invention is implemented through the following technical solutions:
[0006] The first invention object of the present invention is:
[0007] Provided is a pure flat wear-resistant jade tile, comprising: a body, a base glaze, a low-temperature jade glaze, a pattern decoration layer and a transparent wear-resistant polishing glaze;
[0008] The low-temperature jade glaze comprises the following raw material components in weight percentage:
[0009] Potassium feldspar 48-75%, kaolin 8-12%, talc 7-12%, wollastonite 8-15%, alumina 3-7%, the sum of all components is 100%;
[0010] The transparent wear-resistant polishing glaze comprises the following raw material components in weight percentage:
[0011] Potassium feldspar 35-50%, kaolin 8-12%, ultrafine corundum powder 8-15%, zinc oxide 6-9%, barium carbonate 7-10%, dolomite 5-10%, wollastonite 10-18%, talc 5-10%, the sum of all components is 100%.
[0012] The further optimization of the pure flat wear-resistant jade ceramic tile of the present invention is:
[0013] The weight percentage chemical composition of the low-temperature jade glaze is:
[0014] SiO2 55~68%, Al2O3 15~21%, Fe2O3 0.1~0.8%, CaO 4.1~7.3%, MgO2.1~3.9%, K2O 3.5~5.5%, Na2O 2.8~3.5%, TiO2 0~0.1%, loss on ignition 0~1.2%, the sum of all components is 100%.
[0015] The further optimization of the pure flat wear-resistant jade ceramic tile of the present invention is:
[0016] The weight percentage chemical composition of the transparent wear-resistant polishing glaze is:
[0017] SiO2 45~55%, Al2O3 15~22%, Fe2O3 0.1~0.3%, CaO 6~12%, MgO 3.2~5.3%, K2O 3.5~5.5%, Na2O 1.1~1.5%, TiO2 0~0.1%, BaO 5.2~7.5%, ZnO5.8~8.2%, loss on ignition 2~5%, the sum of all components is 100%.
[0018] The further optimization of the pure flat wear-resistant jade ceramic tile of the present invention is:
[0019] The base glaze comprises the following raw material components in weight percentage:
[0020] Potassium feldspar 30-40%, kaolin 4-8%, nepheline 7-15%, brightener 12%-18%, zirconium silicate 5-11%, quartz 15-20%, calcined talc 1-5%, the sum of all components is 100%;
[0021] 1.0% to 1.5% by weight of auxiliary raw materials are added, wherein the added auxiliary raw materials include sodium tripolyphosphate and methyl cellulose.
[0022] The further optimization of the pure flat wear-resistant jade ceramic tile of the present invention is:
[0023] The weight percentage chemical composition of the base glaze is:
[0024] SiO2 50~60%, Al2O3 25~32%, Fe2O3 0.1~0.8%, CaO 0.1~0.8%, MgO0.3~1.5%, K2O 3.2~4.1%, Na2O 1.2~1.8%, TiO2 0~0.1%, ZrO2 3~7%, loss on ignition 0~0.8%, the sum of all components is 100%.
[0025] The further optimization of the pure flat wear-resistant jade ceramic tile of the present invention is:
[0026] The specific gravity of the bottom glaze slurry is 1.85-1.95 g / ml, the flow rate is 30-60 seconds (100 ml volt cup), and the glaze amount is 450-700 g / m 2 ;
[0027] The amount of low-temperature jade glaze applied is 300-500 g / m 2 ;
[0028] The pattern decoration layer is a pattern layer formed by printing patterns and zirconium white ink on low-temperature jade glaze by a digital inkjet machine; the inkjet amount of the zirconium white ink is 5-30g / m 2 , using the opacity effect of zirconium white ink to achieve a three-dimensional jade effect;
[0029] The specific gravity of the transparent wear-resistant polishing glaze is 1.85-1.95 g / ml, the flow rate is 30-60 seconds (100 ml volt cup), and the glaze amount is 700-900 g / m 2 .
[0030] The second object of the present invention is:
[0031] A method for preparing the above-mentioned pure flat wear-resistant jade ceramic tile is provided, which comprises the following preparation steps:
[0032] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0033] S2. Applying low-temperature jade glaze to the brick body A to obtain a brick body B;
[0034] S3. Printing a pattern and zirconium white ink onto the brick body B to obtain a brick body C;
[0035] S4. Apply transparent wear-resistant glaze to the brick body C to obtain a brick body D;
[0036] S5. The brick body D is fired at high temperature to obtain a brick body E;
[0037] S6. The brick body E is subjected to thick polishing to obtain the pure flat wear-resistant jade-like ceramic tile.
[0038] The preparation method of the pure flat wear-resistant jade ceramic tile of the present invention is further optimized as follows:
[0039] The high temperature firing time in step S5 is 55 to 70 minutes, and the firing temperature is 1155° C. to 1175° C.;
[0040] While firing at high temperature, the tiles are tilted and conveyed to increase the number of contact points between the tiles and the sticks, avoiding stick marks and water ripples caused by one side of the tiles hanging in the air during transportation.
[0041] The preparation method of the pure flat wear-resistant jade ceramic tile of the present invention is further optimized as follows:
[0042] The thick polishing described in step S6, i.e. using diamond bevel teeth and high-tooth hard grinding blocks, increases the polishing amount of the glaze surface to eliminate stick marks and water ripples produced during the firing process, and the glaze surface brightness after polishing is 30 to 95 degrees.
[0043] The preparation method of the pure flat wear-resistant jade ceramic tile of the present invention is further optimized as follows:
[0044] It includes one or a combination of the following features:
[0045] The base glaze comprises the following preparation steps:
[0046] According to the ratio of the base glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added, and the mixture is finely ground by ball mill into a glaze slurry with a sieve residue of 0.1% to 0.3% by mass on a 325-mesh sieve and a water content of 23% to 27% by mass, and after three high-intensity iron removal processes, the base glaze is prepared;
[0047] The low-temperature jade glaze comprises the following preparation steps:
[0048] According to the ratio of jade glaze, all raw materials in corresponding proportions are selected, and then appropriate amount of water is added, and the mixture is finely ground by ball mill into a glaze slurry with a sieve residue of 0.3% to 0.5% by mass on a 325-mesh sieve and a water content of 28% to 32% by mass. After the ball milling is qualified, the slurry is discharged, and after screening, iron removal, homogenization and aging, the low-temperature jade glaze slurry is prepared;
[0049] The transparent wear-resistant polishing glaze comprises the following preparation steps:
[0050] According to the ratio of transparent wear-resistant polished glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added and finely ground by ball mill into a glaze slurry with a sieve residue mass percentage of 0.3% to 0.5% on a 325-mesh sieve and a water content of 28% to 32% by mass. After ball milling, the slurry is discharged, and after screening, iron removal, homogenization and aging, the transparent wear-resistant polished glaze is prepared.
[0051] The present invention focuses on the following key technologies:
[0052] (I) Preparation of jade glaze:
[0053] Ordinary polished glaze products usually print inkjet patterns on the bottom glaze layer. Due to the low whiteness of the body, the bottom glaze layer is usually required to have strong covering power and no sense of transparency. In contrast, the present invention prints the pattern and zirconium white ink on the low-temperature jade glaze layer by adding a layer of semi-transparent low-temperature jade glaze. Due to the low temperature and translucent properties of the low-temperature jade glaze, the zirconium white ink and the pattern fuse with it to produce a vague and hazy jade texture. Therefore, the formula composition of the jade glaze directly affects the jade texture of the product. The main component of jade is calcium magnesium silicate. In order to achieve the jade effect of jade, the present invention mainly makes adjustments and optimizations in the following aspects based on the existing glaze formula:
[0054] (1) Introducing silicate components through potassium feldspar:
[0055] Potassium feldspar and sodium feldspar are common silicate minerals. Both potassium feldspar and sodium feldspar are commonly used low-temperature fluxes in ceramic production. Potassium feldspar has a higher initial melting point, which is conducive to the discharge of gas in the body. Its firing range is also wider than that of sodium feldspar. It begins to decompose and melt at a melting point of 1130-1450℃, which is conducive to the discharge of gas in the body and glaze. Silicic acid components are introduced through potassium feldspar to achieve a composition similar to that of jade.
[0056] (2) Introducing calcium and magnesium components to improve jade texture:
[0057] The main component of jade is calcium magnesium silicate. Commonly used raw materials for glaze containing calcium and magnesium components mainly include calcite, dolomite, calcined talc, wollastonite, etc. Calcite and dolomite decompose at high temperatures to produce more CO2 gas, which is easy to cause glaze pinholes, concave glaze, anti-fouling and other problems, while calcined talc and wollastonite have a small ignition loss and basically do not produce gas at high temperatures. Therefore, the present invention introduces calcium and magnesium components by adding calcined talc and wollastonite.
[0058] (II) Preparation of transparent wear-resistant polishing glaze:
[0059] The formula structure and composition of the surface glaze layer (transparent wear-resistant glaze) directly affect the performance indicators of the product glaze, such as wear resistance, anti-fouling, and flatness. In order to eliminate rod marks and water ripples and achieve a flat glaze effect, the present invention adopts a polishing process that increases the amount of polishing, that is, the product is required to have a thicker glaze layer to protect the pattern texture. However, the thicker the glaze, the more difficult it is to discharge the gas in the body and glaze during firing, resulting in more residual pores after the product is fired, and more open pores on the surface of the product after polishing, which affects the product's anti-fouling and wear resistance. Therefore, the thicker the glaze layer, the higher the technical requirements. Based on this, the present invention mainly optimizes and adjusts the formula of transparent wear-resistant glaze from the following aspects.
[0060] (1) Introducing ultrafine corundum powder to increase the wear resistance of polishing glaze:
[0061] The wear resistance of glaze is related to hardness and toughness. The higher the hardness of the glaze, the better the wear resistance; the better the toughness, the better the wear resistance. The best wear resistance can only be achieved when the hardness and toughness of the glaze are appropriate. For the transparent polished glaze layer, too much crystal precipitation in the glaze layer will affect the gloss and transparency of the glaze. Therefore, under the premise of controlling the crystallization of the glaze layer, introducing some network-forming oxides such as quartz (SiO2) and corundum (Al2O3) powder (the Mohs hardness of corundum is 9) into the glaze layer is beneficial to improve the hardness of the glaze.
[0062] To this end, the present invention optimizes and adjusts the SiO2 and Al2O3 contents and the silicon-aluminum ratio in the glaze formula of the transparent wear-resistant polishing glaze. Specifically, while appropriately reducing the SiO2 content (46-48% to ensure sufficient glass network formers), 8-15% of ultrafine corundum powder is introduced to increase the Al2O3 content and reduce the silicon-aluminum ratio. A large number of test results in the present invention show that reducing the silicon-aluminum ratio in the formula to between 3.7 and 4.8 (part of the ultrafine corundum powder introduced does not melt at high temperatures and is evenly distributed in the polishing glaze in the form of residual corundum microcrystals) can greatly improve the wear resistance of the product while ensuring that the polishing glaze has sufficient transparency. At the same time, the addition of corundum significantly increases the initial melting temperature of the polishing glaze, which is beneficial to the discharge of gases in the body and glaze. Theoretically, the more corundum is added, the better. However, since corundum is difficult to melt at high temperatures, the porosity of the glaze will continue to increase with the increase in the amount of corundum crystals. This indicates that during the sintering process, the presence of crystals in the glass may hinder the movement of pores to the surface. The aggregated closed pores adhering to the crystals may lead to a decrease in surface tension, thereby reducing the wear resistance and antifouling properties of the glaze and making it unstable. The present invention concludes through experiments that the introduction of 8-15% of ultrafine corundum powder has the most significant effect, which can not only significantly improve the wear resistance of the glaze, but also maintain the good transparency of the glaze layer.
[0063] (2) Introduction of wollastonite:
[0064] The main function of calcium oxide (CaO) in glaze is flux, which reduces the high-temperature viscosity of glaze and improves the gloss and chemical stability of glaze. At high temperature, CaO reacts with Al and Si to generate microcrystals such as calcium feldspar and wollastonite, which can enhance the hardness and wear resistance of glaze. CaO in glaze formula is mainly introduced in the form of calcite and wollastonite, but during high-temperature calcination, calcite will be decomposed by heat to produce a large amount of CO2 gas, resulting in glaze bubbles and pinholes on the glaze, affecting the appearance and physical properties of the product. The main components of wollastonite (CaO·SiO2) are silicon and calcium, which does not contain volatile components. When it is used to replace limestone and quartz, the glaze will not cause glaze bubbles and pinholes due to the gas produced by high-temperature decomposition. While enhancing the texture, it also improves the wear resistance, anti-fouling and acid-alkali resistance of the glaze. The experimental results of the present invention show that when the amount of wollastonite added is 8% to 18%, the glaze has the best performance in terms of anti-fouling, wear resistance and acid-alkali resistance.
[0065] (3) Introducing appropriate amounts of zinc oxide and magnesium oxide:
[0066] Zinc oxide (ZnO) has a good fluxing effect, which can reduce the expansion coefficient of the glaze, improve the thermal stability of the product, and improve the toughness of the glaze. In addition, ZnO can enhance the color of the glaze and expand the temperature range of the glaze. However, ZnO has a strong tendency to crystallize in the glaze melt. Excessive ZnO will cause the glaze to lose transparency due to crystallization, so the general dosage is 4% to 8%, which is better. Magnesium oxide (MgO) can release free oxygen at high temperature in the glaze, destroy the network structure, and reduce the viscosity of the glaze melt. It is a good high-temperature flux component. Although under high temperature conditions, Na2O and K2O in the glaze formula can form a low eutectic with Al2O3 and SiO2, which plays a role in reducing the firing temperature of the glaze. However, the excessive introduction of Na2O and K2O will significantly increase the thermal expansion coefficient of the surface glaze and reduce the chemical stability and thermal stability of the surface glaze. The experimental results of the present invention show that the method of partially replacing Na2O and K2O with ZnO and MgO can improve the transparency and glossiness of the glaze to a certain extent while ensuring that the firing temperature does not fluctuate significantly over a large range, thereby improving the anti-fouling texture of the glaze and improving the color development performance of the glaze.
[0067] (III) Optimization of firing process:
[0068] The present invention adopts a single high-temperature firing process to produce pure flat wear-resistant jade tiles. During the firing process, the firing performance of the green body, the base glaze and the polishing glaze must be taken into consideration. Due to the large amount of glaze and the large water content of the brick body, the problems of explosion and cracking caused by the green body drying and draining too quickly must also be considered. Therefore, while optimizing the glaze formula composition, the optimization selection of the firing process system for preparing pure flat wear-resistant jade tiles by single high-temperature firing is also extremely critical.
[0069] In the research process of the present invention, according to the sintering characteristics of the green body, through a large number of tests and combined with the high-temperature microscope melting performance analysis of the glaze, combined with the melting characteristics of the base glaze, low-temperature jade glaze, and transparent wear-resistant polishing glaze, the firing process system of the pure flat wear-resistant jade tile was optimized and adjusted:
[0070] (1) Reduce the speed of the kiln rollers to reduce the speed of brick conveying, and appropriately extend the firing time (55 to 75 minutes) so that the bricks have sufficient time and temperature to drain and exhaust. At the same time, increase the temperature in the front zone of the kiln and strengthen the oxidizing atmosphere so that the volatile components are fully oxidized and volatilized before entering the high-temperature zone of the kiln, reducing the amount of gas phase discharged from the glaze in the high-temperature zone, thereby reducing the problems of pinholes, concave glaze, and anti-fouling caused by glaze bubbling.
[0071] (2) Adjust the tilt of the ceramic tile transmission. The existing glazed tile production adopts stick transmission. Since the ceramic tile is fired at high temperature, the stick is more easily deformed by heat. In addition, due to the gravity of the ceramic tile, the stick is easy to produce an arc. The ceramic tile body softens due to heat at high temperature. The soft body moves in the arc-shaped stick, and the body is concave, resulting in unevenness on the surface of the body, thus producing stick marks and water ripples. The present invention adjusts the tilt of the ceramic tile transmission to increase the contact support points between the ceramic tile and the stick, avoiding the ceramic tile unilaterally suspended in the air during the transmission process to produce stick marks and water ripples.
[0072] (IV) Optimization of polishing process:
[0073] Although the above adjustments are made in many aspects, the stick marks and water ripples cannot be completely eliminated. For this reason, the present invention further optimizes the polishing process, that is, increases the polishing amount in the polishing process, polishes away the stick marks and water ripples, and achieves a flat glaze effect. The existing glaze polishing process usually includes three processes: rough grinding, fine grinding and waxing. The present invention mainly optimizes and adjusts the following processes:
[0074] Use hard helical and high-tooth grinding blocks as polishing tools. The grinding block is mainly composed of resin-bonded 120-150 mesh diamond abrasives; the arrangement is a combination of helical and high teeth. The unique tooth arrangement design of the helical hard grinding block can quickly deep polish and flatten the glaze surface, reducing wear marks. BRIEF DESCRIPTION OF THE DRAWINGS
[0075] Figure 1 This is a physical picture of the pure flat wear-resistant jade ceramic tile prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0076] In order to make the application, technical scheme and advantages of the present invention more clear, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the embodiments are only used to illustrate the present invention, but not to limit the protection scope of the present invention. All simple improvements to the preparation method of the present invention under the premise of the concept of the present invention belong to the protection scope of the present invention.
[0077] Example 1
[0078] A method for preparing a pure flat wear-resistant jade tile comprises the following steps:
[0079] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0080] The specific gravity of the base glaze slurry is 1.90 g / ml, the flow rate is 36 seconds (100 ml volt cup), and the glaze amount is 500 g / m 2 ;
[0081] S2. Applying low-temperature jade glaze to the brick body A to obtain a brick body B;
[0082] The specific gravity of the low-temperature jade glaze is 1.90 g / ml, the flow rate is 36 seconds (100 ml volt cup), and the spraying amount is 400 g / m 2 ;
[0083] S3. Printing a pattern and zirconium white ink onto the brick body B to obtain a brick body C;
[0084] The pattern decoration layer is a pattern layer formed by printing patterns and zirconium white ink on low-temperature jade glaze by a digital inkjet machine; the inkjet amount of the zirconium white ink is 12g / m 2 ;
[0085] S4. Apply transparent wear-resistant glaze to the brick body C to obtain a brick body D;
[0086] The specific gravity of the transparent wear-resistant polishing glaze is 1.88g / ml, the flow rate is 35 seconds (100ml volt cup), and the glaze amount is 820g / m 2 ;
[0087] S5. The brick body D is fired at high temperature to obtain a brick body E;
[0088] The high temperature firing time is 58 minutes, and the firing temperature is 1160°C;
[0089] While firing at high temperature, the tiles are tilted and moved so that there are more points of contact between the tiles and the sticks, thus avoiding the stick marks and water ripples caused by the tiles hanging on one side during the conveying process.
[0090] S6. The brick body E is subjected to thick polishing to obtain the pure flat wear-resistant jade-like ceramic tile.
[0091] The base glaze comprises the following raw material components in weight percentage:
[0092] Potassium feldspar 36%, kaolin 7%, nepheline 12%, brightener 16%, zirconium silicate 9%, quartz 16%, calcined talc 4%;
[0093] 1.0% to 1.5% by weight of auxiliary raw materials are added, wherein the added auxiliary raw materials include sodium tripolyphosphate and methyl cellulose.
[0094] The base glaze comprises the following preparation steps:
[0095] According to the ratio of the base glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added and finely ground by ball mill into a glaze slurry with a 325-mesh sieve residue mass percentage of 0.1% to 0.3% and a water mass percentage of 23% to 27%. After three high-intensity iron removal processes, the base glaze is prepared.
[0096] The low-temperature jade glaze comprises the following raw material components in weight percentage:
[0097] Potassium feldspar 63%, kaolin 10%, talc 11%, wollastonite 13%, alumina 3%;
[0098] The low-temperature jade glaze comprises the following preparation steps:
[0099] According to the ratio of jade glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added and finely ground by ball mill into a glaze slurry with a sieve residue mass percentage of 0.3% to 0.5% on a 325-mesh sieve and a water content of 28% to 32% by mass. After ball milling, the slurry is discharged, and after screening, iron removal, homogenization and aging, the low-temperature jade glaze slurry is prepared.
[0100] The transparent wear-resistant polishing glaze comprises the following raw material components in weight percentage:
[0101] Potassium feldspar 36%, kaolin 10%, ultrafine corundum powder 10%, zinc oxide 8%, barium carbonate 7%, dolomite 8%, wollastonite 13%, talc 8%;
[0102] The transparent wear-resistant polishing glaze comprises the following preparation steps:
[0103] According to the ratio of transparent wear-resistant polished glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added and finely ground by ball mill into a glaze slurry with a sieve residue mass percentage of 0.3% to 0.5% on a 325-mesh sieve and a water content of 28% to 32% by mass. After ball milling, the slurry is discharged, and after screening, iron removal, homogenization and aging, the transparent wear-resistant polished glaze is prepared.
[0104] Example 2
[0105] A method for preparing a pure flat wear-resistant jade tile comprises the following steps:
[0106] S1. preparing a body and applying a base glaze to the body to obtain a brick body A;
[0107] The specific gravity of the base glaze slurry is 1.88 g / ml, the flow rate is 38 seconds (100 ml volt cup), and the glaze amount is 550 g / m 2 ;
[0108] S2. Applying low-temperature jade glaze to the brick body A to obtain a brick body B;
[0109] The specific gravity of the low-temperature jade glaze is 1.91 g / ml, the flow rate is 36 seconds (100 ml volt cup), and the spraying amount is 420 g / m 2 ;
[0110] S3. Printing a pattern and zirconium white ink onto the brick body B to obtain a brick body C;
[0111] The pattern decoration layer is a pattern layer formed by printing patterns and zirconium white ink on low-temperature jade glaze by a digital inkjet machine; the inkjet amount of the zirconium white ink is 15g / m 2 ;
[0112] S4. Apply transparent wear-resistant glaze to the brick body C to obtain a brick body D;
[0113] The specific gravity of the transparent wear-resistant polishing glaze is 1.92g / ml, the flow rate is 38 seconds (100ml volt cup), and the glaze amount is 850g / m 2 ;
[0114] S5. The brick body D is fired at high temperature to obtain a brick body E;
[0115] The high temperature firing time is 58 minutes, and the firing temperature is 1165°C;
[0116] While firing at high temperature, the tiles are tilted and moved so that there are more points of contact between the tiles and the sticks, thus avoiding the stick marks and water ripples caused by the tiles hanging on one side during the conveying process.
[0117] S6. The brick body E is subjected to thick polishing to obtain the pure flat wear-resistant jade-like ceramic tile.
[0118] The raw material composition and other related preparation processes of Example 2 are the same as those of Example 1.
[0119] Comparative Example 1
[0120] The difference between Comparative Example 1 and Example 1 is that low-temperature jade glaze is not applied, and other processes are the same.
[0121] Comparative Example 2
[0122] The difference between Comparative Example 2 and Example 1 is that ordinary glaze polishing is used, and other processes are the same.
[0123] Comparative Example 3
[0124] The difference between Comparative Example 3 and Example 1 is that the polishing process adopts a common process, and the other processes are the same.
[0125] The difference between Comparative Example 4 and Example 1 is that during the high-temperature firing process of Comparative Example 4, the tiles are not tilted for conveying and positioning, and other processes are the same.
[0126] The specific preparation process and glaze effect comparison of the examples and comparative examples are shown in Table 1.
[0127] Table 1
[0128]
[0129] The present invention adjusts and optimizes the composition ratio of the low-temperature jade glaze formula, prints the pattern and zirconium white ink on the low-temperature jade glaze layer, and the pattern and zirconium white ink fuse and react with the low-temperature glaze layer, thereby forming an ethereal jade texture. At the same time, by adjusting and optimizing the transparent wear-resistant polishing glaze formula, the purpose of improving the wear resistance of the glaze surface is achieved by introducing ultra-fine corundum powder, wollastonite, etc. In addition, combined with the optimization adjustment of the firing and polishing processes, a flat glaze effect is achieved. The wear-resistant flat jade tile product of the present invention has a wear resistance of 6000 revolutions (level 4) and a Mohs hardness of level 4 as tested by the Foshan Quality and Metrology Supervision and Inspection Center.
[0130] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0131] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0132] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0133] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0134] Unless otherwise stated, percentages and parts are by mass.
[0135] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0136] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
Claims
1. A pure flat wear-resistant jade tile, characterized by: It includes: body, base glaze, low-temperature jade glaze, pattern decoration layer and transparent wear-resistant polishing glaze; The low-temperature jade glaze comprises the following raw material components in weight percentage: Potassium feldspar 48-75%, kaolin 8-12%, talc 7-12%, wollastonite 8-15%, alumina 3-7%, the sum of all components is 100%; The transparent wear-resistant polishing glaze comprises the following raw material components in weight percentage: Potassium feldspar 35-50%, kaolin 8-12%, ultrafine corundum powder 8-15%, zinc oxide 6-9%, barium carbonate 7-10%, dolomite 5-10%, wollastonite 10-18%, talc 5-10%, the sum of all components is 100%.
2. The flat wear-resistant jade ceramic tile according to claim 1, characterized in that: The weight percentage chemical composition of the low-temperature jade glaze is: SiO2 55~68%, Al2O3 15~21%, Fe2O3 0.1~0.8%, CaO 4.1~7.3%, MgO2.1~3.9%, K2O 3.5~5.5%, Na2O 2.8~3.5%, TiO2 0~0.1%, loss on ignition 0~1.2%, the sum of all components is 100%.
3. The flat wear-resistant jade ceramic tile according to claim 1, characterized in that: The weight percentage chemical composition of the transparent wear-resistant polishing glaze is: SiO2 45~55%, Al2O3 15~22%, Fe2O3 0.1~0.3%, CaO 6~12%, MgO 3.2~5.3%, K2O 3.5~5.5%, Na2O 1.1~1.5%, TiO2 0~0.1%, BaO 5.2~7.5%, ZnO5.8~8.2%, loss on ignition 2~5%, the sum of all components is 100%.
4. The flat wear-resistant jade ceramic tile according to claim 1, characterized in that: The base glaze comprises the following raw material components in weight percentage: Potassium feldspar 30-40%, kaolin 4-8%, nepheline 7-15%, brightener 12%-18%, zirconium silicate 5-11%, quartz 15-20%, calcined talc 1-5%, the sum of all components is 100%; 1.0% to 1.5% by weight of auxiliary raw materials are added, wherein the added auxiliary raw materials include sodium tripolyphosphate and methyl cellulose.
5. The flat wear-resistant jade ceramic tile according to claim 4 is characterized in that: The weight percentage chemical composition of the base glaze is: SiO2 50~60%, Al2O3 25~32%, Fe2O3 0.1~0.8%, CaO 0.1~0.8%, MgO0.3~1.5%, K2O 3.2~4.1%, Na2O 1.2~1.8%, TiO2 0~0.1%, ZrO2 3~7%, loss on ignition 0~0.8%, the sum of all components is 100%.
6. The flat wear-resistant jade ceramic tile according to claim 1, characterized in that: The specific gravity of the base glaze slurry is 1.85-1.95 g / ml, the flow rate is 30-60 seconds, and the glaze amount is 450-700 g / m 2 ; The amount of low-temperature jade glaze applied is 300-500 g / m 2 ; The pattern decoration layer is a pattern layer formed by printing patterns and zirconium white ink on low-temperature jade glaze by a digital inkjet machine; the inkjet amount of the zirconium white ink is 5-30g / m 2 ; The specific gravity of the transparent wear-resistant polishing glaze is 1.85-1.95 g / ml, the flow rate is 30-60 seconds, and the glaze application amount is 700-900 g / m 2 .
7. A method for preparing the flat wear-resistant jade ceramic tile according to claim 1, characterized in that: The pure flat wear-resistant jade ceramic tile comprises the following preparation steps: S1. preparing a body and applying a base glaze to the body to obtain a brick body A; S2. Applying low-temperature jade glaze to the brick body A to obtain a brick body B; S3. Printing a pattern and zirconium white ink onto the brick body B to obtain a brick body C; S4. Apply transparent wear-resistant glaze to the brick body C to obtain a brick body D; S5. The brick body D is fired at high temperature to obtain a brick body E; S6. The brick body E is subjected to thick polishing to obtain the pure flat wear-resistant jade-like ceramic tile.
8. The method for preparing the flat wear-resistant jade ceramic tile according to claim 7, characterized in that: The high temperature firing time in step S5 is 55 to 70 minutes, and the firing temperature is 1155° C. to 1175° C.; While firing at high temperature, the tiles are tilted and conveyed to increase the contact and support points between the tiles and the sticks. The method for preparing a pure flat wear-resistant jade tile according to claim 7 is characterized in that: The thick polishing described in step S6, i.e. using a diamond bevel-tooth and high-tooth hard grinding block, increases the polishing amount of the glaze surface, and the glaze surface brightness after polishing is 30 to 95 degrees.
9. The method for preparing the flat wear-resistant jade ceramic tile according to claim 7, characterized in that: It includes one or a combination of the following features: The base glaze comprises the following preparation steps: According to the ratio of the base glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added, and the mixture is finely ground by ball mill into a glaze slurry with a sieve residue of 0.1% to 0.3% by mass on a 325-mesh sieve and a water content of 23% to 27% by mass, and after three high-intensity iron removal processes, the base glaze is prepared; The low-temperature jade glaze comprises the following preparation steps: According to the ratio of jade glaze, all raw materials in corresponding proportions are selected, and then appropriate amount of water is added, and the mixture is finely ground by ball mill into a glaze slurry with a sieve residue of 0.3% to 0.5% by mass on a 325-mesh sieve and a water content of 28% to 32% by mass. After the ball milling is qualified, the slurry is discharged, and after screening, iron removal, homogenization and aging, the low-temperature jade glaze slurry is prepared; The transparent wear-resistant polishing glaze comprises the following preparation steps: According to the ratio of transparent wear-resistant polished glaze, all raw materials in corresponding proportions are selected, and then an appropriate amount of water is added and finely ground by ball mill into a glaze slurry with a sieve residue mass percentage of 0.3% to 0.5% on a 325-mesh sieve and a water content of 28% to 32% by mass. After ball milling, the slurry is discharged, and after screening, iron removal, homogenization and aging, the transparent wear-resistant polished glaze is prepared.
Citation Information
Patent Citations
Ceramic tile with purely flat glaze and manufacturing method for ceramic tile
CN103274767A
High-temperature wear-resistant frit, wear-resistant glaze using same and glazed tile
CN111533449A
Wear-resistant glaze and preparation method thereof
CN112390532A
Cited By
Ceramic tile with super-thick-layer semi-transparent jade grease slurry coating luster
CN119874195A